BIPV Form Factor as an Approach for the Energy Performance of Buildings Exemplified for the Location of Tabriz (Iran) - Azami, Ahadollah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Building form and envelope surfaces play a significant role in energy performance assessment and the generated energy potential of the building integrated photovoltaics (BIPV) concept in early-stage design. To increase the energy efficiency level, form factor (FF) is proposed as a helpful tool that provides a strong relationship between the exposed surface areas and the treated floor area (TFA). This research aimed at developing a parametric study to determine the related balance (correlation) between the TFA and needed BIPV area in the form enclosure to meet specific primary energy demand (SPED) according to the passive house standard (PHS). For this purpose, various form types including square, rectangle, L, and T shapes-which is derived of four modular cubes- classified based on the same form factor (FF). Optimal form selection per group carried out through the BIPV potential evaluation for the exposed surfaces in six azimuths separately. Afterward, BIPV efficiency level examined by its utilization factor and coverage index scenarios based on façade and roof combination priorities. The results indicate that the generated energy sufficiency is affected by the form configuration and its orientation. Additionally, the optimal BIPV-based FF value of 0.71 implies the priority of roof-based scenarios for less BIPV utilization. Finally, the correlation value for the BIPV coverage index relative to the total envelope for the optimal forms and orientation is higher than 0.92, which can be extended to other forms in different locations as an assessment model.

ÖZ: Bina formunun ve kabuğunun yüzeyleri, enerji performans değerlendirmesinde ve erken tasarım aşamasında bina entegre fotovoltaik (BIPV) konseptinin enerji potansiyeli için önemli bir rol oynamaktadır. Enerji verimliliği seviyesini artırmak için form faktörü (FF), yapının dışa açık yüzey alanları ile ısıtma / soğutma için gerekli enerji kullanım alanı (TFA) arasında güçlü bir ilişki sağlayan araç olarak önerilmektedir. Bu araştırma, pasif ev standardına (PHS) göre spesifik birincil enerji talebini (SPED) karşılamak için enerji kullanım alanı (TFA) ile ihtiyaç duyulan bina entegre fotovoltaik (BIPV) alanı arasındaki ilgili dengeyi (korelasyonu) belirlemek amacıyla parametrik bir çalışma geliştirmeyi amaçlamıştır. Bu amaç doğrultusunda, dört modüler küpten elde edilen kare, dikdörtgen, L ve T gibi çeşitli form türleri aynı form faktörüne (FF) göre sınıflandırılmıştır. Her grup için uygun modüler form seçimi gerçekleştirilerek altı ayrı azimuta dışa açık yüzeyler için ayrı ayrı bina entegre fotovoltaik (BIPV) potansiyeli değerlendirilmiştir. Sonrasında, cephe ve çatı kombinasyon önceliklerine göre kullanım faktörü ve kapsama endeksi senaryoları ile bina entegre fotovoltaik (BIPV) verimlilik düzeyi incelenmiştir. Sonuçlara göre, üretilen enerji yeterliliğinin form konfigürasyonundan ve oryantasyonundan etkilendiğini göstermektedir. Ek olarak, 0,71'lik BIPV tabanlı form faktör (FF) değeri, daha az bina entegre fotovoltaik (BIPV) kullanımı için çatı tabanlı senaryoların önceliğini ifade eder. Son olarak, uygun formlar ve oryantasyon için toplam içeriğe göre bina entegre fotovoltaik (BIPV) kapsam endeksinin korelasyon değeri 0,92'den yüksektir ve bir değerlendirme modeli olarak farklı yerlerdeki diğer formlara genişletilebilir.
Doctor of Philosophy in Architecture. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2021. Supervisor: Assoc. Prof. Dr. Harun Sevinç
Keywords: Thesis Tez; Architecture Department; Building Integrated Photovoltaics--Design and Construction--Climate-responsive design--Tebriz (Iran); Building-integrated photovoltaic systems; Buildings--Energy conservation; Architecture and energy conservation; Sustainable engineering--Solar Energy; Buildings--Environmental engineering; Building integrated photovoltaics (BIPV); Building Envelope; Building Form; Form Factor; Energy Performance